2016
DOI: 10.1007/jhep10(2016)107
|View full text |Cite
|
Sign up to set email alerts
|

Full top quark mass dependence in Higgs boson pair production at NLO

Abstract: Abstract:We study the effects of the exact top quark mass-dependent two-loop corrections to Higgs boson pair production by gluon fusion at the LHC and at a 100 TeV hadron collider. We perform a detailed comparison of the full next-to-leading order result to various approximations at the level of differential distributions and also analyse non-standard Higgs self-coupling scenarios. We find that the different next-to-leading order approximations differ from the full result by up to 50 percent in relevant differ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
257
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(265 citation statements)
references
References 133 publications
8
257
0
Order By: Relevance
“…In fact, for the double Higgs production cross section (where the main contribution comes from the region in which the invariant mass of the di-Higgs final state is larger than the threshold 2m t ) it has been shown that the NLO HEFT prediction overestimates the full NLO result by a 14% and 24% for E cm = 14 and 100 TeV [6,29] (and with deviations of the same order for the shape of the invariant mass distribution). Of course, for triple Higgs production the exact NLO result is not available.…”
Section: Phenomenological Resultsmentioning
confidence: 99%
“…In fact, for the double Higgs production cross section (where the main contribution comes from the region in which the invariant mass of the di-Higgs final state is larger than the threshold 2m t ) it has been shown that the NLO HEFT prediction overestimates the full NLO result by a 14% and 24% for E cm = 14 and 100 TeV [6,29] (and with deviations of the same order for the shape of the invariant mass distribution). Of course, for triple Higgs production the exact NLO result is not available.…”
Section: Phenomenological Resultsmentioning
confidence: 99%
“…Finally, exact NLO results became available in refs. [14,15] using a numerical approach for the computation of the two-loop virtual corrections. Based on these results the transverse momentum resummation has been considered in ref.…”
Section: Jhep03(2018)048mentioning
confidence: 99%
“…We aim to study double Higgs boson production via the process gg → HH. Numerical NLO results are available [14,15], however the calculation of cross sections is computationally expensive and we want to provide an independent cross check in the high-energy region. We wish to provide results in terms of compact analytic expressions which can be used to construct simple approximations or can be used directly in the kinematic region in which they are valid.…”
Section: Jhep03(2018)048mentioning
confidence: 99%
See 1 more Smart Citation
“…At the LHC, Higgs boson pair production is known to be the primary process where one can use to determine this coupling [6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Nonetheless, it is expected to be a challenging measurement due to its low production cross section predicted in the SM, σ(pp → hh) SM ∼ 40 fb at the 14-TeV LHC [20][21][22][23][24][25][26][27][28][29][30]. In the SM, tree-level Higgs trilinear and quartic self couplings are given as…”
Section: Introductionmentioning
confidence: 99%